Weak biodiversity connectivity in the European network of no-take marine protected areas - Assis, J. (2021)
The need for international cooperation in marine resource management and conservation has been reflected in the increasing number of agreements aiming for effective and well-connected networks of Marine Protected Areas (MPAs). However, the extent to which individual MPAs are connected remains mostly unknown. Here, we use a biophysical model tuned with empirical data on species dispersal ecology to predict connectivity of a vast spectrum of biodiversity in the European network of marine reserves (i.e., no-take MPAs). Our results highlight the correlation between empirical propagule duration data and connectivity potential and show weak network connectivity and strong isolation for major ecological groups, resulting from the lack of direct connectivity corridors between reserves over vast regions. The particularly high isolation predicted for ecosystemstructuring species (e.g., corals, sponges, macroalgae and seagrass) might potentially undermine biodiversity conservation efforts if local retention is insufficient and unmanaged populations are at risk. Isolation might also be problematic for populations' persistence in the light of climate change and expected species range shifts. Our findings provide novel insights for management directives, highlighting the location of regions requiring additional marine reserves to function as stepping-stone connectivity corridors. (C) 2021 Elsevier B.V. All rights reserved.